2018
DOI: 10.1002/hed.25047
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging versus laryngovideostroboscopy in precancerous and malignant vocal fold lesions

Abstract: Background This is a comparative analysis of the diagnostic accuracy of narrow band imaging (NBI) and laryngovideostroboscopy (LVS) in the assessment of premalignant and malignant vocal fold lesions. Methods A prospective analysis was performed on 105 consecutive patients with vocal fold lesions. The NBI and LVS were obtained before the microsurgery. Results The NBI and LVS showed no significant differences in identifying premalignant and malignant pathologies. However, in analysis restricted to identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
(64 reference statements)
1
23
0
Order By: Relevance
“…Sakthivel and colleagues 25 reported a sensitivity of 100% when using NBI with WLE. Rzepakowska and colleagues 26 demonstrated a sensitivity of 98.8% when using NBI in diagnosing premalignant and malignant laryngeal lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakthivel and colleagues 25 reported a sensitivity of 100% when using NBI with WLE. Rzepakowska and colleagues 26 demonstrated a sensitivity of 98.8% when using NBI in diagnosing premalignant and malignant laryngeal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Mehlum and colleagues 17 reported that Ni type IV and V had a high diagnostic accuracy for detecting laryngeal cancer with a sensitivity of 89% and specificity of 82%. Rzepakowska and colleagues 26 compared laryngovideostroboscopy (LVS) and NBI in malignant laryngeal pathologies and demonstrated that LVS was sensitive (97.6%) in detecting malignant laryngeal pathologies. The LVS findings correlated strongly with NBI findings using the Ni classification with a spearman correlation value of 0.54.…”
Section: Discussionmentioning
confidence: 99%
“…However, different studies have reported mixed results for narrow-band imaging endoscopy diagnoses of vocal fold leukoplakia and early vocal fold cancer, with accuracy rates ranging from 70.6 per cent to 94.5 per cent, and sensitivity values ranging from 58.6 per cent to 97.0 per cent. [17][18][19][20][21] To improve the accuracy and consistency of the differential diagnosis of benign and malignant vocal fold lesions obtained using the Ni classification with narrow-band imaging endoscopy, we proposed a new diagnostic classification of vocal fold leukoplakia that comprises subdivisions based on narrowband imaging endoscopy. 9 This new diagnostic classification of vocal fold leukoplakia aimed to overcome the blocking effect of leukoplakia on mucosal microvessels, thereby improving the consistency between the narrow-band imaging endoscopy diagnosis and the pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Two reviewers summarized all data using standard forms. The diagnostic odds ratios (DORs), 4‐31,35‐37 summary receiver operating characteristic (SROC) curves, areas under the curves (AUCs), 4‐31,35‐37 and the extent of inter‐rater agreement 17,22,23,26 associated with NBI studies were evaluated, as was the (comparative) diagnostic accuracy of WLE. Each DOR was calculated as: (true positive (TP)/false positive [FP])/(false negative [FN]/true negative [TN]) with 95% confidence intervals (CIs); we used random‐effects models that considered both within‐ and between‐study variations.…”
Section: Methodsmentioning
confidence: 99%